Acute and Repeated Dose 28-Day Oral Toxicity Study of the Aqueous Extracts from the Leafy Stem and Fruit of Pedalium murex D.Royen EX.L in Wistar Rats - Gérard Bessan Dossou-Agoin; Maxime Machioud Sangaré-Oumar; Téniola Isabelle Sacramento; Mariette Sindété; Egnon Jacques Hougbénou-Houngla; Nounagnon Darius Tossavi; Simon Azonbakin; Adam Gbankoto (Journal of Toxicology)
Background. Pedalium murex (P. murex) is used in folk medicine for treatment of male infertility. However, scientific data on its safety are limited. Objective. This study was carried out to assess the acute and repeated dose 28-day oral toxicity of the aqueous extracts from P. murex leafy stem and fruit in Wistar rats. Methods. The acute toxicity test was performed according to the line 423 of the Organization for Economic Cooperation and Development (OECD) guidelines. The rats were randomly divided into three groups (n = 3). The control group received distilled water, while the experimental groups were given at a single dose, 5000 mg/kg of each extract. The repeated dose 28-day oral toxicity was performed according to the line 407 of the OECD guidelines. 35 rats divided into 7 groups of 5 male rats each were daily treated for 28 days with each extract at 200 mg/kg, 400 mg/kg, and 800 mg/kg, respectively. The in-life parameters were recorded during the follow-up. At the end of this study, organ weights, hematology, biochemistry, and histology parameters were analyzed. Results. In the acute oral toxicity test, there was no morbidity or mortality related to the treatments. Both extracts belong therefore to category 5 of the globally harmonized system (GHS) of classification. In the repeated dose 28-day oral toxicity test, both extracts did not alter animal’s behavior. However, both extract administration led to proteinuria and renal damages. Conclusion. P. murex leafy stem and fruit aqueous extracts exhibited potential nephrotoxicity. Therefore, care should be taken when they are used over an extended period.